2005
DOI: 10.1093/humrep/dei194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the insecticide amitraz, an α2-adrenergic receptor agonist, on human luteinized granulosa cells

Abstract: Amitraz inhibited basal and hCG-stimulated progesterone but not estrogen production. The inhibitory action of amitraz and its antagonism by yohimbine suggest that alpha2-adrenergic receptors are expressed by luteinized human granulosa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…42 Norepinephrine may then be able to interact with ovarian a-and b-receptors present on granulose cells. 43,44 Bovine luteal cells are also reported to synthesize NE in a similar way 45 and presumably this also occurs in intraovarian nerve fibres. Recent study revealed dopamine receptors expressed by endocrine cells of the follicle and the corpus luteum, which suggests a complex role of dopamine in the regulation of ovarian processes.…”
Section: Discussionmentioning
confidence: 94%
“…42 Norepinephrine may then be able to interact with ovarian a-and b-receptors present on granulose cells. 43,44 Bovine luteal cells are also reported to synthesize NE in a similar way 45 and presumably this also occurs in intraovarian nerve fibres. Recent study revealed dopamine receptors expressed by endocrine cells of the follicle and the corpus luteum, which suggests a complex role of dopamine in the regulation of ovarian processes.…”
Section: Discussionmentioning
confidence: 94%
“…The concentration of P 4 in the cell culture medium after treatments was measured by radioimmunoassay (RIA) as previously described . Briefly, an antibody against P 4 raised in rabbit and 125 I‐radiolabeled P 4 (MP Biomedical; Solon, OH, USA), along with a sheep antirabbit secondary antibody (Chemicon; Boronia, Victoria, Australia), were used for the measurement of P 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Granulosa cells were donated by women with normal reproductive physiology who were undergoing ART to treat male infertility. Granulosa cell isolation has been described previously [53]. Briefly, pooled aspirates for each woman were isolated by centrifugation at 107× g for 10 min, followed by two cycles of rinsing and then the cell suspension was re-suspended in Dulbecco’s modified Eagle’s HAMS F12 (DMEM-F12; GIBCO, Invitrogen Corporation) mediumsupplemented with 10% FBS (GIBCO Invitrogen Corporation), penicillin/streptomycin 5000 IU/mL and 5000 μg/mL respectively (Thermo Scientific), insulin (5 μg/mL), transferin apohuman (5 μg/mL), selenium sodium selenite (5 ng/mL) buffered with 1.2 g/L NaHCO 3 (Pfizer).…”
Section: Methodsmentioning
confidence: 99%